Chapter 13 — Developing a Preventive Pruning Program in Your Community: Mature Trees - Edward F. Gilman; Amanda Bisson (EDIS)
ENH1063, a 14-page full color fact sheet by Edward F. Gilman and Amanda Bisson, is part of the Urban Forest Hurricane Recovery Program series. It describes seven main objectives, along with pruning types that help meet those objectives, which can be expanded or shortened to meet site conditions and customer expectations. It also describes how to determine a pruning cycle and how to implement a preventative pruning plan for mature trees. Published by the UF Department of Environmental Horticulture, September 2007.